Multiple Representations and the Understanding of Taylor Polynomials - Habre, Samer (2009)
The study of Maclaurin and Taylor polynomials entails the comprehension of various new mathematical ideas. Those polynomials are initially discussed at the college level in a calculus class and then again in a course on numerical methods. This article investigates the understanding of these polynomials by students taking a numerical methods class at the Lebanese American University in Beirut. The class adopted a closed laboratory format where Mathematica was used extensively. Results show that the added graphical dimension due to the use of the software does not necessarily contribute to a further understanding of the topics under examination. In fact, each subject of the study exhibited a unique mode of understanding: For one, it was purely graphical, for another analytical/numerical, and for the third all three modes complemented each other.